Chorotypes d’îles et d’archipels : une proposition - Matheus Menegatto; Hervé Théry (Confins)
Space sparsity, low amount of resources, maritimity, facility to recognize geographical and political frontiers, endemism and social differences in relation to other lands are some features of the islands. However, there are many situations related to the insular spaces and we chose the chorotypes (complex graphic models of spatial relationships common to two or more places on Earth) to show some possibilities to understand the insularity. To do so, we brought examples of islands and archipelagoes in Brazil and around the world.